Overview of Efforts Improve Health Literacy in Education Units Ministry of Health Republic of Indonesia - Khatimah, Kusnul; Rohmah , Nur; Guspita Dewi, Irma (Faculty of Public Health Mulawarman University, Indonesia, 2025)
Background : The low level of health literacy among school students can affect their healthy living behavior and health status. This internship examines Health teaching materials applied in teaching tools to support students' understanding of health, especially basic health, mental health, nutrition, reproductive health, and clean and healthy living behavior (PHBS). Objective : Knowing the application of health teaching tools in the independent curriculum in education units in improving students' knowledge, attitudes and skills towards Indonesia Emas 2045. Research Methods/ Implementation Methods : in the process of reporting internship activities using the interview method and using secondary data to complement the data. Results : The Ministry of Health has made efforts to improve health literacy using health teaching tools that are implemented in an independent curriculum. This effort also involves other parties, namely the Ministry of Education, Culture, Research and Technology and the Ministry of Religion as the party that oversees educational institutions in Indonesia. The health teaching tools are made for each level of student education Through these efforts, the Ministry of Health is also committed to improving health literacy so that it can form positive characters towards health in every school age group. Thus, groups of school children can have the knowledge and awareness to implement preventive efforts so as to avoid various health problems with various health teaching materials such as posters, infographics, animated videos, videos, broadcast materials, playing cards, comics, books by reaching a total of 296,261 total downloads of teaching tools. Of the 154 health teaching tools that are already available on the Ayo Sehat website and the Merdeka Mengajar Platform (PMM) as of October 15, 2024, there are 11,799 schools that have downloaded health teaching tools. Conclusion/Lesson Learned : The Ministry of Health develops health teaching tools that are integrated into the curriculum in educational units at the PAUD, SD, SMP, SMA / equivalent levels. Reaching a total of 296,261 total downloads of teaching tools, Of the 154 health teaching tools that are already available on the Ayo Sehat website and the Merdeka Mengajar Platform (PMM) as of October 15, 2024, there are 11,799 schools that have downloaded health teaching tools.